Implementasi Data Mining dengan Metode Regresi Linear untuk Prediksi Hasil Penjualan di PT Awitama Cyndo Wahana - Pradita, Anggi; Rasiban (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The increase in the number of new entrepreneurs in Indonesia is influenced by technological developments, easier access to information, and government support. This increases the need for legal services such as making business permits and business agreements. Lack of understanding of the legal aspects of business can hinder business growth. PT Awitama Cyndo Wahana, a legality management service provider, has great potential to support new entrepreneurs. However, this company has not utilized sales data to predict future sales. This research uses sales data from PT Awitama Cyndo Wahana to predict sales using the linear regression method. The test results show that the Root Mean Squared Error (RMSE) is 458618.289, the Absolute Error is 183084.456, and the Relative Error is 0.98%. These results indicate that the prediction model has an adequate level of accuracy, although there are some prediction errors. The practical implication of this research is that PT Awitama Cyndo Wahana can use these sales predictions to plan more effective marketing strategies and make data-based business decisions, so that they can better support the growth of new entrepreneurs.